Synthesis and characterization of Ni-incorporated mesoporous silica material for its potential applications in oligomerization of glycerol. (21st September 2022) - Ilavarasi Jeyamalar, J.; Krishnaveni, M.; Kannan, Chellapandian
Abstract: Rectangular shaped nickel incorporated mesoporous silica material (Ni-MSi) was synthesized by a simple sol-gel method from sodium silicate and hydrocarbon template and it was characterized by various spectroscopic techniques such as XRD, FT-IR, TGA/DTA, SEM, TEM and nitrogen adsorption. The results confirmed the formation of a mesoporous material with high thermal stability and large porosity. The synthesized catalyst was applied for glycerol conversion. Conversion of glycerol increases with increased of temperature. However the selectivity of diglycerol is 85% at 100 °C, selectivity of triglycerol is 50% at 150 °C and polyglycerol selectivity is 59% at 200 °C. When the temperature increases, more number of glycerol molecules involved in the etherification reaction. The products of the reactions are characterized by 1 H NMR, 13 C NMR and mass spectroscopy. The results of the characterization confirmed the formation of diglycerol, triglycerol and polyglycerol. Graphical Abstract: UF0001